Wspólnototwórczy wymiar przekładu. Casus XXI-wiecznych przekładów górnośląskich / Community-Creating Function of Translation Case of Twenty-First-Century Translations into Upper-Silesian - Pospiszil, Karolina (Przekłady Literatur Słowiańskich, 2019)
Existence of Upper-Silesian ethic minority has been confirmed by two national censuses carried out in the years 2002 and 2011. It is also the largest minority residing in the territory of the Republic of Poland. However, the Polish state does not recognize the existence of Upper Silesians in legal terms. At the same time, for Upper Silesians themselves the struggle for recognition of their culture, language and community is a serious matter. In the present article the author discusses the role of creating and strengthening Upper-Silesian community played by culture, especially by literature and literary translation.